Pengaruh Media Sosial, Brand Awareness, Dan Brand Image Terhadap Loyalitas Konsumen Grab - Rifqi Arya Sandhi; Nora Andira Brabo (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
In the current era of globalization, the development of internet-based social media is increasingrapidly, this is followed by the increasing number of social media users around the world. The development of information and communication technology increases easier and faster interactionbetween customers and advertisers. Information is more quickly obtained through digital media. Technological developments take part in the dissemination of information, especially in advertising through social media. One of the activities that can be facilitated by technological advances is transportation. One of the most popular online transportation companies in Indonesia is Grab. This study will discuss the Influence of Social Media, Brand Awareness and Brand Image on Grab Consumer Loyalty. The subjects in this study were consumers who had used the Grab application. The research method used is quantitative. Data collection was done by using a questionnaire. The research population was 100 respondents. The data analysis used is statistical analysis in the form of SPSS 22 multiple linear regression.